PENGARUH WORD OF MOUTH DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA INTERIOR MUTIARA GADING SERPONG KABUPATEN TANGERANG - Apriyadi, Oby; Maulana Irfanudin, Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of word of mouth and product quality on purchasing decisions at Interior Mutiara Gading Serpong, Tangerang Regency, both partially and simultaneously. The method used is quantitative with 96 respondents as a sample. This study also uses various tests such as validity, reliability, classical assumptions, correlation coefficients, regression, determination, and hypotheses. The results show that word of mouth has a significant effect on purchasing decisions, with a regression equation of Y = 13.014 + 0.691 X1. The t-value of 15.528> t-table 1.665 and a significance of 0.000 <0.050, so H0 is rejected and H1 is accepted. This means that partially word of mouth has a positive and significant effect. Product quality also has a significant effect with a regression equation of Y = 8.502 + 0.494 X2. The calculated t value is 14.013 > t table 1.661 and the significance is 0.000 < 0.050, so H0 is rejected and H2 is accepted. Simultaneously, word of mouth and product quality have a significant effect on purchasing decisions, with the regression equation Y = 8.640 + 0.429 X1 + 0.229 X2. The calculated f value is 154.556 > ft table 3.09 and the significance is 0.000 < 0.050. Therefore, H0 is rejected and H3 is accepted